Zeolite application for the enhancement of methane production in landfill leachate - Pauzan, Mohammad Arif Budiman (2016)
High concentration of organics, ammonia, and heavy metals in landfill leachate are harmful to the environment as well to human’s health. These high toxicity compounds may dampen microorganisms’ activity in anaerobic reactor, particularly the methanogens. The aim of this research is to investigate the potential toxicity and biodegradability of landfill leachate under methanogenic conditions using batch microcosm assays, which are anaerobic toxicity assays (ATA) and biochemical methane potential (BMP) methods, and to enhance its biodegradability using natural zeolite (clinoptilolite) and synthetic zeolite (Sigma 96096). Leachate sample was collected from Seelong Sanitary Landfill, Johor. Response Surface Methodology (RSM) was used to determine the adsorption of ammoniacal nitrogen (NH3-N) present in leachate on clinoptilolite and Sigma 96096 based on three variables including dosage, particle size, and percentage of leachate to distilled water. Based on the optimized operational conditions, the maximum removal of NH3-N for clinoptilolite and Sigma 96096 were 90.61% and 56.67%, respectively; with the dosage, particle size, and percentage of leachate to distilled water of 2 g/L, 50 mm and 50% for clinoptilolite, and for Sigma 96096 at 4 g/L, 150 mm and 50%, respectively. Biodegradability assays were conducted on varied concentrations of leachate using two anaerobic biomass from Indah Water Konsortium (IWK), Ulu Tiram, Johor and KULIM Palm Oil Mill Effluent Treatment Plant (KULIM), Kulai, Johor. Based on ATA, no significant inhibition was recorded for 10% leachate concentration supplied with clinoptilolite and seeded with KULIM biomass. Meanwhile, for BMP, the assay contained 5% of leachate with Sigma 96096 and IWK seed recorded the highest conversion efficiency of 43.03%. Hence, the ATA and BMP assays are beneficial to predict the production potential of methane from waste in full scale reactor.